Global assessment of hepatic safety in novel immunotherapies: a systematic review and meta-analysis - Ye, Minyan; Dong, Yinuo; Li, Xiaoyun; Zhi, Yang; Lu, Yuping; Tang, Jieting; Zhong, Wei; Lei, Xiaohong; Mao, Yimin; Huang, Sha; Song, Yanyan (Frontiers in Immunology, 2026)
BackgroundThis study explored whether integrating innovative immunotherapies targeting costimulatory or co-inhibitory pathways beyond standard PD-1, PD-L1, and CTLA-4 treatments affects hepatic adverse events. We further analyzed liver-related side effects in patients with cancer receiving these novel therapies alone or in combination with others.MethodsClinical studies on immunotherapies targeting molecules such as LAG-3, TIGIT, TIM-3, VISTA, CD47, ICOS, CD40, and B7-H3 were retrieved from PubMed, Embase, Cochrane Library, and Web of Science. Data from eligible studies that reported liver-related adverse events until May 2024 were included.ResultsThis analysis included 63 studies involving 7,327 patients. Among these, randomized controlled trials demonstrated that adding LAG-3 or TIGIT inhibitors to established therapies did not increase the risk of elevated hepatic enzyme levels or hepatitis. CD27-CD70-targeted monotherapy showed a strong association with elevated transaminase levels. Dual therapies combining 4-1BB agonists with PD-1/PD-L1 inhibitors resulted in >15% all-grade transaminase elevation, whereas CD40 agonists paired with immunotherapy resulted in >4% high-grade elevations. Immunotherapy-chemotherapy combinations showed high transaminase elevation rates. Overall, the incidence of elevated liver enzyme levels was similar between the single-agent and dual immunotherapy groups. The addition of chemotherapy or targeted therapy to single-agent immunotherapy increases the incidence of adverse events associated with elevated liver enzyme levels. The incidence of liver enzyme adverse events continued to increase with the addition of immunotherapy to the combination regimens. Cholestatic enzyme elevations were prominent in CD27-CD70 monotherapy and CD40 agonist combinations.ConclusionsThis meta-analysis suggests adding LAG-3 or TIGIT inhibitors to existing therapies may not significantly increase hepatic toxicity. It reviewed adverse events from novel immunotherapies alone or combined with PD-1/PD-L1/CTLA-4 inhibitors, targeted agents, or chemotherapy. These findings have important clinical implications.